1969
DOI: 10.1002/pol.1969.150070208
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of aromatic aldehydes. II. Cationic cyclopolymerization of phthalaldehyde

Abstract: Phthalaldehyde was found to undergo cyclopolymerization with ease by several cationic catalysts and by γ‐ray irradiation. The polymer was composed entirely of the dioxyphthalan unit, as confirmed by infrared spectroscopy and ready decomposition to monomer. The enhanced polymerizability of phthalaldehyde as compared with other aromatic aldehydes was explained in terms of the intermediate‐type or, preferably, concerted propagation scheme. The conversion reached a saturation value of 87% in about 1 hr in methylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 16 publications
5
60
0
Order By: Relevance
“…These results indicated that the copolymers had no BzA-BzA sequences, and were consistent with previous reports that BzA homopolymerization did not proceed. [10][11][12][13] On the other hand, copolymerization failed in polar solvents such as dichloromethane, at 0 C, and/or in the absence of an added base. In these cases, only IBVE homopolymers were obtained, as confirmed by 1 H NMR analysis.…”
Section: Copolymerization Of Bza With Ibve Using Various Lewis Acidsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results indicated that the copolymers had no BzA-BzA sequences, and were consistent with previous reports that BzA homopolymerization did not proceed. [10][11][12][13] On the other hand, copolymerization failed in polar solvents such as dichloromethane, at 0 C, and/or in the absence of an added base. In these cases, only IBVE homopolymers were obtained, as confirmed by 1 H NMR analysis.…”
Section: Copolymerization Of Bza With Ibve Using Various Lewis Acidsmentioning
confidence: 99%
“…Homopolymerization of aromatic aldehydes is known to be especially difficult. [10][11][12] In fact, their homopolymerizations have never been achieved except in the case of benzaldehyde (BzA) derivatives with special structures. 10,12,13 In contrast, polymers were obtained from both BzA and a simple derivative in copolymerizations with styrene (St) or isoprene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aso et al were successful in developing an in situ IR method for monitoring the monomer concentration for poly(phthalaldehyde) polymerization, but were limited by the temperature control. 12,13 The variable temperature NMR method for measuring monomer concentration and polymer thermodynamics has been disclosed before but has not been applied to very low ceiling temperatures polymers such as polyaldehydes. [14][15][16][17][18] In this paper, variable temperature 1 H NMR was used to measure the polymer ceiling temperature and to provide additional insight into the thermodynamics of polymerization for several low ceiling temperature polyaldehydes.…”
mentioning
confidence: 99%